Financial Management and Record Keeping as Correlates of Teachers’ Service Delivery in Public Secondary Schools in Anambra State - Samuel Ogechukwu Otugo; Zita Chika Obi (PT. Altaf Publishing Corp, 2026)
This study investigated the relationship between financial management, record keeping, and teachers’ service delivery in public secondary schools in Anambra State. A correlational research design was adopted, guided by two research questions and two hypotheses. The population comprised 6,598 teachers, from which 660 teachers were selected using proportionate random sampling. Data were collected using a validated questionnaire and analyzed with Pearson Product Moment Correlation Coefficient at a 0.05 significance level. Findings revealed a very strong positive correlation between financial management and teachers’ service delivery (r = 0.872) and a strong positive correlation between record keeping and service delivery (r = 0.774), both statistically significant. The results indicate that effective financial governance and systematic record keeping significantly enhance teachers’ service delivery. The study recommends strengthening participatory financial management and continuous training in modern, including digital, record-keeping practices.